KEAJAIBAN CIPTAAN DAN IMPLIKASINYA DALAM PEMBELAJARAN - Nangsari Ahmad (Universitas Islam Negeri Raden Fatah Palembang, 2012)
Man presented on this earth - to borrow a term in computer science - with a hardware and software. The brain is the hardware and the software is reasonable. According recognized expert neuroscience (neuroscience) has 100 biliun brain nerve cells (neurons), and each cell can make 20,000 relationships. Relationships that determine a person's potential. In addition, human beings are endowed almighty with a software, the reason (thought). The reason to process data from the five senses (data entry of hearing, sight, smell, taste, touch or sense) to mind that are stored in the brain as a "memory" after a reasonable pack, mostly, in the symbols language and all the accessories (intonation, rhythm, sound pressure, movement, expression, facial expressions, body language and others). Apparently only people who have that ability. Animals also communicate, but do not use the language, at least, are not as effective as human language. Humans use language not only to communicate but also to other things, such as man can cure himself of the disease in misery with positive thinking. They also determine the attitude, spirit, ideals, hopes, and their establishment in the language, which is then stored as a memory in the brain there. In addition, human blessed with multiple intelligences and three ways of thinking (psychological, emotional, mental or spiritual). The implications of all this for learning, and even education as a whole, is very large. At best a teacher would not work membelajarkan students, if the students did not want membelajarkan himself. Teacher is a facilitator, motivator, and dynamic. Educating is managing learner's conscience so that he became dignified and powerful members of society to society, nation, homeland and nation.